2014
DOI: 10.1007/s10236-014-0767-9
|View full text |Cite
|
Sign up to set email alerts
|

A geometric method to study water and sediment exchange in tidal harbors

Abstract: The exchange flow of water and sediment between a harbor and the surrounding waters can be geometrically decomposed into three main components: tidal filling, horizontal, and vertical exchange flows.The method is applied to analyze available measurements at two important harbor basins in Belgium. The geometric analysis can also be applied to the results of a numerical model of hydrodynamics and sediment transport, provided it has sufficient horizontal, vertical, and temporal resolutions to capture the dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…Sediment import through advection is apparent both in the ADCP backscatter dataset (Section 4.3.2) as in the ensembles based on the OBS dataset (Section 4.3.1). This hypothesis is consistent with the analysis of the sediment exchange mechanisms between the harbor of Zeebrugge and the North Sea presented by Vanlede and Dujardin (2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Sediment import through advection is apparent both in the ADCP backscatter dataset (Section 4.3.2) as in the ensembles based on the OBS dataset (Section 4.3.1). This hypothesis is consistent with the analysis of the sediment exchange mechanisms between the harbor of Zeebrugge and the North Sea presented by Vanlede and Dujardin (2014).…”
Section: Discussionsupporting
confidence: 92%
“…A freshwater front of 1-m height in a water column of 15 m has a propagation speed of 0.6 m/s (β 1 = 0), which would (assuming no net water exchange) induce a depth averaged return flow of only 0.05 m/s into the harbor. This is consistent with an analysis of the velocity field around the harbor entrance of Zeebrugge which shows that water exchange due to density currents is small compared with the total exchange flow (Vanlede and Dujardin 2014).…”
Section: Influence Of Freshwater Inflow On Sediment Importsupporting
confidence: 90%
See 2 more Smart Citations
“…The SSC revealed that the estuaries turbidity maximum was intensified due to the deep water project, especially in the wet season, and an upstream shift and extension of the ETM zone occurred. Vanlede and Dujardin (2014) apply geometric analysis method to study the exchange flow and sediment between a harbor and the surrounding water. The method can provide some insight into the complex relationship between hydrodynamics and sediment concentration that determines harbor siltation.…”
mentioning
confidence: 99%